ANALISIS KELAYAKAN PANGAN SEBAGAI HASIL HUTAN - Triyono Puspitojati (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2015)
Food plants have been cultivated in various types of forest estates. However, contribution of forestry to support food security had been less recognized because foods derived from forests were not recorded as forest products. The objective of this literature reviewwasto analyze the feasibility of food obtained from forests as forest products. Sustainable use of forests as a source of food was used as a criteria to determine the feasibility. The results showed that the use of forests as a source of food has been practiced well in five periods of human life interacted with forests. In Period I and II, forests become a major or sole source of food. In Period III, forests become a starting place of the food plant development. In Period IV, food plants are cultivated during forest regeneration. In Period V, food plants in the category of tree, palm, shrub and seasonal plant are cultivated in forest areas of industrial forest estate, rural forest estate, village forest, community forestry and NWFP-forest estate. Based on comprehensive literatures on scientific as well as legal literatures, food derived from forests was proper to be determined as forest products.